Sistemi upravljanja sadržajem - pojam i karakteristike / Content management systems: Concept and features - Dejan S. Milenković; Marina V. Jovanović-Milenković; Zoran A. Radojičić (Vojnotehnički Glasnik, 2010)
Rad predstavlja kratak prikaz osnova programskog rešenja koje je u poslednjih desetak godina okupiralo sve veće i ozbiljne poslovne organizacije koje svoje poslovanje, celokupno ili delimično, zasnivaju na principima Internet tehnologija i elektronskog poslovanja. Sistemi upravljanja sadržajima nametnuli su se kao potreba da se izvrši potpuna automatizacija poslovanja jedne organizacije. U perspektivi, upravljanje dokumentima komandno-informacionih sistemima Vojske Srbije biće zasnovano na sistemima upravljanja sadržajima. / Introduction The paper explains the importance and the role of content management systems, gives an overview of the functionality required by such systems and makes a categorization of existing content management systems, thus performing, to some extent, a systematization of this area. Internet technologies and e-business Electronic business is a set of business activities that occur by ICT, especially Internet. CMS existence is conditioned by the development of Internet technology. Basic terminology, problem and solution The basic terms of which problems are considered in this paper are Content, Content Management and Content Management System. Content management systems demand Content management systems demand is reflected in the following: (1) complex structure and a hierarchy of target groups are major challenges for the selection and implementation of an adequate system of content management in decision-making processes; (2) timely adoption of key decisions and their implementation is currently a considerable advantage over competitors; (3) by applying modern information and communication technologies and service-oriented architecture, content, especially documents, management provides security and protection of information in the process of content managing. Content management systems types This article describes the following types of content management systems: Document Management System, Digital Asset Management, Web Content Management and Learning Content Management. Content management systems basic parts The main parts of the content management system are: (1) Content integration, including any content manipulation (input, processing, display); (2) Version control, older versions of files are stored in the database (date of creation/change, and optional comment). Thanks to version control, web site can be restored later (rolled-back) to the previous version; (3) Workflow, allows defining processes in a few steps concerning the creation, review and approval of content publishing; (4) Content repositorium (relational, object or XML databases) greatly improves reuse and content management, especially when these items have a high repetition level; (5) Users management and their privileges; (6) User interface. Display of client and administrative console is done through a web browser; (7) Applications represent an addition to content management systems (business rules, API functions, search, forum, etc.) Content management systems classification Content management systems classification can be performed by different elements: (1) by type, where the content management system is a framework or system; (2) by license; (3) by used technology; (4) by price. The paper briefly explains the classification. Conclusion Future direction of research of content management system applications in the Serbian Army would be based on the advantages and disadvantages of electronic document management system repositories, for example realistic management processes and data flows within the command and information system.